Geospatial Analysis of Wisconsin Honey Bee Hives - Sorenson, Ellen (My University, 2013)
The purpose of this study was to focus on the influence of apiary size and proximity to urban environments in relation to the overall health of honey bee hives in Wisconsin. This research was a response to the outbreak of Colony Collapse Disorder (CCD) that hit the United States in 2005. Survey data was used in conjunction with Geographical Information Systems (GIS) and the North American Statistics Service (NASS) crop cover data to create maps used to determine how hive health might relate to crop cover. Geospatial technologies were used to assess the health consequences of hive locations to shed light on the human-environmental interactions and regional factors from which conclusions were drawn.
Color poster with text and maps.
Keywords: Geospatial data; Honey bee hives--Wisconsin; Posters